Measuring the Impact of Public Understandings of Risk from Urban and Industrial Development on Community Psychosocial Well-Being: a Mixed Methods Strategy - Baldwin, Cathy; Cave, Ben; Rawstorne, Patrick (International Journal of Community Well-Being, 2020)
As the science of well-being moves towards an understanding of the influence of social experiences shared by many on individual and group-level well-being (‘community well-being’), a new approach to measuring well-being is required. It needs to bridge the contextually-specific social experiences best uncovered by social research methods, and psychological diagnoses made using conventional psychometric scales and diagnostic interviews. We build on our previous work on a new psychosocial model of a major influence on contemporary community well-being, the process by which people form, maintain and change their understandings of risk from urban and industrial projects, and any subsequent effects on individual psychosocial well-being . We utilise this model, and propose a mixed qualitative and quantitative methodology to argue for; 1) the incorporation of the emic (subject’s) perspective in the conceptual underpinnings of measurement scales; and 2) the synthesis of quantitative and qualitative assessments of well-being. This gives validity and contextual precision to scales which measure experiences of well-being that are geographically and socio-culturally-located. The resulting data offers both context of scale, and depth of insight. Additionally, our proposition combines theories and methods from psychology, social anthropology, sociology, social epidemiology, public health and community development. This evinces the importance of drawing on broad ranging perspectives to develop tools which capture the complex and multi-dimension nature of well-being - where psychological responses are shaped by collective social experiences.